All-fibre Q-switching YDFL operation with bismuth-doped fibre as saturable absorber. Issue 8 (4th May 2018) - Muhammad, A. R.; Haris, H.; Arof, H.; Tan, S. J.; Ahmad, M. T.; Harun, S. W.
Abstract: We demonstrate the generation of a passively Q-switched ytterbium-doped fibre laser (YDFL) using a bismuth-doped fibre (BDF) as a solid-state fibre saturable absorber (FSA) in a ring cavity. The BDF used has a wide and low absorption band of 5 dB/m at the 1.0 μm region due to the ion transition of 3 P 0 → 3 P 1 that occurs around the region. When introduced into a YDFL laser cavity, a stable Q-switched pulse operation was observed and the pulse repetition rate was proportional to the input pump power. It was limited to 72.99 kHz by the maximum power that the laser diode could supply. Meanwhile, the pulse width decreased from 12.22 to 4.85 μs as the pump power was increased from 215.6 to 475.6 mW. The finding suggests that BDF could be used as a potential SA for the development of robust, compact, efficient and low cost Q-switched fibre lasers operating at 1 micron region.